2014
DOI: 10.1080/14786435.2014.906758
|View full text |Cite
|
Sign up to set email alerts
|

Pairing, pseudogap and Fermi arcs in cuprates

Abstract: We use Angle Resolved Photoemission Spectroscopy (ARPES) to study the relationship between the pseudogap, pairing and Fermi arcs in cuprates. High quality data measured over a wide range of dopings reveals a consistent picture of Fermiology and pairing in these materials. The pseudogap is due to an ordered state that competes with superconductivity rather then preformed pairs.Pairing does occur below T pair ∼ 150K and significantly above Tc, but well below T* and the doping dependence of this temperature scale… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
28
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 48 publications
10
28
0
3
Order By: Relevance
“…At lower T , the transport in La 1.85 Sr 0.15 Cu 1−y Ni y O 4 has a coherent description in the framework of Fermi-liquid theory, where Kohler's rule is derived under single-relaxation-time approximation with the assumption of small τ -anisotropy over Fermi surface [63,64]. Fulfillment of the rule when ρ 0 is changed by changing temperature indicates nearly T -independent frequency distribution of the phonons involved [65] and is consistent with Fermi-arc length in cuprates being constant [66,67] rather than decreasing with decreasing temperature [68]. Ni doping can restore antiferromagnetic fluctuations [30,69] that give additional T -dependence in nearly-antiferromagnetic-metals magnetoresistance via correlation length ξ AF (T ), OMR∝ξ 4 AF (T )ρ −2 0 (Ref.…”
Section: (B-d)mentioning
confidence: 90%
“…At lower T , the transport in La 1.85 Sr 0.15 Cu 1−y Ni y O 4 has a coherent description in the framework of Fermi-liquid theory, where Kohler's rule is derived under single-relaxation-time approximation with the assumption of small τ -anisotropy over Fermi surface [63,64]. Fulfillment of the rule when ρ 0 is changed by changing temperature indicates nearly T -independent frequency distribution of the phonons involved [65] and is consistent with Fermi-arc length in cuprates being constant [66,67] rather than decreasing with decreasing temperature [68]. Ni doping can restore antiferromagnetic fluctuations [30,69] that give additional T -dependence in nearly-antiferromagnetic-metals magnetoresistance via correlation length ξ AF (T ), OMR∝ξ 4 AF (T )ρ −2 0 (Ref.…”
Section: (B-d)mentioning
confidence: 90%
“…For example, previous ARPES measurements showed clear evidence that the antinodal gap enhances with temperature at optimally doped Bi 2 Sr 2 CuO 6+δ (Bi-2201) [47,48] and La 2−x Sr x CuO 4 (La-214) [49]. A recent study on Bi-2201 further reported that the anomalous temperature dependence of the measured gap, from slight underdoping to slight overdoping, extends to temperatures above T c (below T * ) [50]. In comparison, the gap remains nearly unchanged below T c in the deeply underdoped region where the pseudogap dominates, but follows the traditional BCS-like temperature dependence in the heavily overdoped region where the SC gap dominates.…”
Section: Introductionmentioning
confidence: 96%
“…One of the most controversial topics in the field of high-temperature superconductivity is the origin of the so-called pseudogap phenomenon observed by various experimental techniques in the underdoped cuprates [1][2][3] at temperatures T * being larger than the superconducting transition temperature T c . A large number of theoretical scenarios have been initially proposed to explain the origin of the pseudogap [4].…”
mentioning
confidence: 99%
“…To model the temperature dependence of the optical conductivity we perform additional calculations, assuming that the gap function follows an effective strong-coupling-like behavior as (T ) = 1 − (T /T CDW ) 3 . The result is shown in Fig.…”
mentioning
confidence: 99%